Mechanisms of spinal cord injury regeneration in zebrafish: a systematic review - Zeynab Noorimotlagh (Iranian Journal of Basic Medical Sciences, 2017)
Objective(s):To determine the molecular and cellular mechanisms of spinal cord regeneration in zebrafish. Materials and Methods: Medical databases of PubMed and Scopus were searched with following key words: Zebrafish; spinal cord injuries; regeneration; recovery of function. The map of mechanisms was performed using Xmind software. Results: Wnt/ß-catenin signaling, L1.1, L1.2, Major vault protein (MVP), contactin-2 and High mobility group box1 (HMGB1) had positive promoting effects on axonal re-growth while Ptena had an inhibitory effect. Neurogenesis is stimulated by Wnt/ß-catenin signaling as well as HMGB1, but inhibited by Notch signaling. Glial cells proliferate in response to fibroblast growth factor (fgf) signaling and Lysophosphatidic acid (LPA). Furthermore, fgf signaling pathway causes glia bridge formation in favor of axonal regeneration. LPA and HMGB1 in acute phase stimulate inflammatory responses around injury and suppress regeneration. LPA also induces microglia activation and neuronal death in addition to glia cell proliferation, but prevents neurite sprouting. Conclusion: This study provides a comprehensive review of the known molecules and mechanisms in the current literature involved in the spinal cord injury (SCI) regeneration in zebrafish, in a time course manner. A better understanding of the whole determining mechanisms for the SCI regeneration should be considered as a main goal for future studies.